Decrease of organochloride pesticides in soil by wild plants. (Experimental biology, 2015)
We have spent screening of 14 plant species on the ability to remediation of soils contaminated with organochlorinepesticides. It was found that due phytostabilization and phytoextraction plants reduced the concentration oforganochlorine pesticides in the original soil to 28% of control.Keywords:.
Keywords: plant; pesticides; phytostabilization; phytoextraction